Big data in public affairs - Mergel, Ines; Isett, Kimberley; Rethemeyer, R. Karl (2016)
This article offers an overview of the conceptual, substantive, and practical issues surrounding "big data" to provide one perspective on how the field of public affairs can successfully cope with the big data revolution. Big data in public affairs refers to a combination of administrative data collected through traditional means and large-scale data sets created by sensors, computer networks, or individuals as they use the Internet. In public affairs, new opportunities for real-time insights into behavioral patterns are emerging but are bound by safeguards limiting government reach through the restriction of the collection and analysis of these data. To address both the opportunities and challenges of this emerging phenomenon, the authors first review the evolving canon of big data articles across related fields. Second, they derive a working definition of big data in public affairs. Third, they review the methodological and analytic challenges of using big data in public affairs scholarship and practice. The article concludes with implications for public affairs. - Reproduced.
Keywords: Public administration; Big data